CEOs’ Financial Background and Non-financial Enterprises’ Shadow Banking Business - Yang, Chen; Shen, Weitao (Frontiers in Psychology, 2022)
In recent years, the "financial-like" behavior of non-financial enterprises has contributed to the “off real to virtual”, which has seriously restricted the virtuous cycle of finance and economy. This study selects non-financial enterprises listed on Chinese A-shares from 2008 to 2019 as the research sample, and empirically analyzes the impact of CEOs’ financial background on the shadow banking business of non-financial enterprises and its mechanism. The results show that: (1) CEOs’ financial background has a positive effect on shadow banking business of non-financial enterprises, among which, the positive effect generated by non-banking financial background is stronger. The conclusions still hold after robustness tests by replacing the measurement of variables, controlling for other shocks, changing the parameter estimation method, and considering the endogeneity problem. (2) The mechanism analysis reveals that the CEOs’ financial background promotes shadow banking by non-financial enterprises mainly by reducing the level of entity investment by enterprises. (3) The heterogeneity analysis finds that, on the one hand, with respect to the internal micro characteristics of enterprises, the positive effect is more significant in state-owned enterprises, non-manufacturing enterprises and non-growth stage enterprises. On the other hand, with respect to the external macro environment, the positive effect is more significant in periods of easy monetary policy, in industries with a higher competition or in regions with a better institutional environment. This study reveals the intrinsic mechanism of CEOs’ financial background and shadow banking of non-financial enterprises, enriches the study of the influencing factors of shadow banking of non-financial enterprises, and provides micro-level empirical support to alleviate the “off real to virtual” of the economy.